What is innovation anyway? Youth perspectives from resource-constrained environments. (June 2016) - Baskaran, Shruthi; Mehta, Khanjan
Abstract: Innovation manifests itself in myriad forms in developing communities. A better understanding of the meaning and rationale for innovation, as perceived by the rapidly-growing youth population in developing countries, is pivotal to the design of practical and sustainable technology innovations and entrepreneurial ecosystems. This article presents the findings of interviews conducted with 271 youth across the rural, semi-urban, and urban areas of Kenya, Tanzania, India and Nicaragua. These provisional narratives explain how the next generation perceives innovation, and illustrates how cultural mechanisms and communal context bias innovative solutions for individual or community needs. The dynamic interdependence between innovation and the socio-cultural context is brought to life by juxtaposing narratives of respondents from Kenya and Tanzania, neighboring countries with starkly different histories. Different perceptions of what constitutes innovation is critical as it varies from location to location and impacts the likelihood of success of different technologies and innovations. Such similarities and differences in the major themes of innovations, driving factors, and rationales can inform and inspire innovators seeking to meld western and indigenous innovation frameworks to foster self-determined improvement of lives and livelihoods. Highlights: We explore how youth in developing communities within four countries view innovation. We discuss perspectives on the definition, rationale and drivers of innovation. Through narratives, we present nuanced indigenous perspectives on innovation. We illustrate how culture and context influence the development of innovation. We chronicle local innovations that are leapfrogging over existing technologies.